Insecticidal activity of four citrus peel oils and oil nanoemulsion formulation against Sitophilus oryzae L. and Corcyra cephalonica (ST.) - Ibrahim, Elmiligy Elsayed Elsayed (2019)
The rice weevil, Sitophilus oryzae and rice moth, Corcyra cephalonica are primary destructive insect pests. The adults and larvae of S. oryzae and the larvae of C. cephalonica feed voraciously on a wide variety of grains causing quantitative and qualitative losses. This study was conducted to evaluate the insecticidal effects of citrus peel oils of sweet orange; Citrus sinensis, green lemon; Citrus aurantifolia, Kaffir lime; Citrus hystrix and calamansi lime; Citrus microcarpa against these two major stored product insects. Essential oils from four species of citrus plants were obtained from Best Formula Industries Company (Kuala Lumpur, Malaysia). The chemical components in these essential oils were identified using gas chromatography/mass spectrometry and they were tested for their insecticidal properties against adults of the rice weevil, S. oryzae L. and the 4th instar larvae of rice moth, C. cephalonica (St.). The major compounds found in tested essential oils were limonene, β-pinene, citronellal, α-terpineol, citronellol, and geraniol. The S. oryzae populations treated with C. hystrix, C. aurantifolia, C. sinensis, C. microcarpa showed contact toxicity with LC50 values of 119.44, 149.94, 183.26, and 341.26 ppm after 72 hours, post exposure, respectively, compared to C. cephalonica populations with the LC50 values of 1176.43, 1889.24, 3965.71, and 6107.51 ppm after 72 hours, post exposure, respectively. In the case of fumigant toxicity, the S. oryzae populations treated with C. hystrix, C. aurantifolia, C. sinensis, C. microcarpa showed toxicity with LC50 values of 96.96, 192.21, 224.22, and 276.99 ppm after 72 hours, post exposure, respectively, compared to C. cephalonica populations with the LC50 values of 533.48, 752.35, 959.82, and 1082.53 ppm after 72 hours, post exposure, respectively. This variation in results and efficacy of essential oils is related to the chemical components of these essential oils. Oil nanoemulsion system was developed for insecticide formulations of the citrus peel oils by constructing ternary phase diagrams, constituted of non-ionic surfactants, carriers, water, and C. hystrix oil as an active ingredient. The non-ionic surfactants were Emersense AM 8025, Triton X-100, and Tween 80. Three oils were used as a carrier (Rapeseed methyl ester, Methyl oleate, and Agnique AMD 810). All phase diagrams revealed a range of 46 to 91% isotropic region. The phase diagram of Agnique AMD 810/Triton X-100/water system gave the largest 91% one phase region, while that of Methyl oleate/Emersense/water system gave the smallest 46% one phase region. The points were selected from the isotropic regions which exhibited high proportion of oil, low proportion of water and adequate proportion of surfactant to mix with the active ingredient and to form oil-in-water (O/W) emulsion. Sixteen formulations miscible with C. hystrix oil were selected. In the stability study, all the selected formulations were stable under centrifugation and storage at room temperature (25°C) and at 54°C. The mean particle size of nano-emulsion ranged between 54.04 to 461.30 nm except for F2, F3, and F15 with mean particle size >500 nm. All sixteen formulations showed surface tension, lower than water. The zeta potential values of all formulations ranged from 42.16 mV to 86.66 mV, except for F2, F3, F4, F6, and F8 were lower than 30 mV. . The value is related to the stability of colloidal dispersions and high zeta potential value will confer stability. In the toxicity study, the formulated oils against the two insects showed the mortality was higher than that of the nonformulated oils. The contact toxicity against the S. oryzae populations showed that the oil nanoemulsion formulations were more toxic with LC50 ranging from 43.46 to117.25 ppm after 72 hours, post exposure, compared to C. cephalonica populations with LC50 ranging from 462.63 to 916.27 ppm. Similarly, the fumigant toxicity against the S. oryzae populations treated with the oil nano-emulsion formulations were more toxic with LC50 ranging from 43.38 to 91.71 ppm after 72 hours post exposure, compared to C. cephalonica populations with LC50 ranging from 405.09 to 494.39 ppm. The findings suggested that the nano-emulsion formulations of C. hystrix essential oil were effective and could be used to control S. oryzae and C. cephalonica.